Sirtuins and Their Implications in the Physiopathology of Gestational Diabetes Mellitus - Katarzyna Zgutka; Marta Tkacz; Marta Grabowska; Wioletta Mikołajek-Bedner; Maciej Tarnowski (Pharmaceuticals)
Gestational diabetes mellitus (GDM) imposes serious short- and long-term health problems for the mother and her child. An effective therapeutic that can reduce the incidence of GDM and improve long-term outcomes is a major research priority and is very important for public health. Unfortunately, despite numerous studies, the molecular mechanisms underlying GDM are not fully defined and require further study. Chronic low-grade inflammation, oxidative stress, and insulin resistance are central features of pregnancies complicated by GDM. There is evidence of the involvement of sirtuins, which are NAD+-dependent histone deacetylases, in energy metabolism and inflammation. Taking these facts into consideration, the role of sirtuins in the pathomechanism of GDM will be discussed.